The Ecclesial Responsibilities of Theologians, Forty Years after Vatican II - Rigali, Norbert (Horizons, 2006)
There was a time when theological discourse occurred generally in either of two modes, as a professor-to-students lecture/dialogue or as a theologian-to-other-theologians scholarly communication of books, journals and professional meetings. This twofold role of teacher and professional colleague defined essentially what a theologian does. Although the theologian's work is still thought of in this way by some, this is no longer an adequate model. Contemporary theologians, to be sure, still bear the responsibilities of professors and professional colleagues, but because of changes in Church and society they now have a new responsibility as well.The most important change in the Catholic Church effected by the Second Vatican Council was arguably the emergence in recent decades of a new kind of laity, a laity empowered to exercise a more active and participatory role in the life and works of the Church. During the same period, moreover, a well-educated laity has grown up in many countries, including the United States.These changes in the Catholic laity—the great majority of whom, of course, are lay persons in relation to the theological profession as well—have had direct repercussions on the vocation of theologians. As the catalogues and sales of religious publishing houses readily show, contemporary theological works are being read by many lay persons who are not theologians. With their more active and participatory role in the Church's life and mission, lay persons now experience a vested interest in theology and its development.